Needs Analysis of English for Specific Purposes (ESP) in Students’ Speaking Materials - Luana Sasabone; Irman; Anwar Taufiq; Nurul Amaliah Hasbi (CV. Eureka Murakabi Abadi, 2024)
Needs analysis is crucial in the development of speaking material and serves as a valuable tool for teachers to create materials that align with the specific requirements and learning goals of the learners. This study aims to investigate needs analysis of English for Specific Purposes (ESP) in students’ speaking materials. This study was conducted in accounting students of Universitas Kristen Indonesia (UKI) Paulus Makassar. The data analysis revealed valuable information regarding the instruction of the ESP course. The study found that ESP classes mostly emphasized speaking skills for accounting students. Furthermore, it has been observed that the ability to talk was deemed more essential compared to other skills. The data analysis facilitated the identification of the fundamental language-related duties within the realm of accounting studies. As conclusion states that accounting students demonstrate a higher level of confidence in their speaking skill when it comes to English, compared to their proficiency in other skills.